Differential DNA methylation patterns in human Schlemm’s canal endothelial cells with glaucoma - Cai, Jingwen (Mol Vis, 2020)
PURPOSE: Schlemm’s canal (SC) endothelial cells derived from donors with or without glaucoma showed different mechanical properties and gene expression. As an important contributor to the regulation of intraocular pressure (IOP) and pathogenesis of primary open-angle glaucoma (POAG), the heritable key epigenetic changes, methylation may play an important role in the physiologic function of SC cells. This study aims to identify differentially methylated CpG sites (DMSs) in primary cultures of human SC cells with or without glaucoma. METHODS: We examined the methylation pattern of seven strains of primary human cells (two glaucoma and five normal SC cell samples), which were isolated and characterized using established protocols. DNA methylation was profiled using Illumina Human Methylation 450 BeadChip. Raw data were extracted and exported using Illumina GenomeStudio software. After quantile normalization, DNA methylation data were analyzed using R package RnBeads in Bioconductor. DMSs were filtered with p ≤ 1E-5, methylation change ≥ 0.1, and false discovery rate ≤ 0.05. The closest genes and the location of each CpG site were annotated using R package FDb.InfiniumMethylation.hg19. Gene Ontology and pathway analysis was performed using WebGestalt. Selected DMSs were validated using the Zymo qMethyl kit. RESULTS: We used five non-glaucoma and two glaucomatous SC cell samples to profile genome-wide DNA methylation using Illumina Infinium Methylation BeadChips. Principle component analysis showed the separation between the glaucoma and control samples. After quality control and differential analysis, we identified 298 highly significant DMSs (p ≤ 1E-5). Among them, 221 DMSs were within 1 kb of a nearby gene. Gene Ontology analysis demonstrated significant enrichment in positive regulation of cell migration, negative regulation of endothelial cell proliferation, and stress fiber and actin filament bundles. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed enrichment in cell adhesion and gap junctions. Several glaucoma-related genes were identified, including TGFBR3, THBS1, PITX2, DAXX, TBX3, TNXB, ANGPT1, and PLEKHA7. We also examined differentially methylated regions (DMRs) near these CpG sites and identified significant DMRs in TBX3, TNXB1, DAXX, and PITX2. CONCLUSIONS: This study represents the first genome-wide DNA methylation profiling in cultured human primary SC cells. The DMSs were enriched in the pathways related to outflow resistance. Several DMRs were validated in glaucoma-associated genes, further suggesting the role of DNA methylation in glaucoma development. This study could provide comprehensive understanding of DNA methylation in glaucoma and its effect on aqueous humor outflow.